Utilization Of Barcode Generator In Android Based Inventory Management Application At BPKH 1 Medan - Ramadhan, M Irsyad; Hafiz, Rahmat (Journal of Computer Science and Informatics Engineering, 2022)
This study aims to design and build an android-based application that can generate QR Barcodes. This application can help the head of the equipment section in overcoming problems that had occurred in the inventory management process. So far, there are still many companies or agencies whose inventory management is done manually and based on books or excel. Problems that often occur are the difficulty of carrying out item data and loss of item ID label data on items that cannot be scanned. The development method used in this research is the Extreme Programming (XP) method, which consists of the planning, design, coding and testing stages of the application. The Extreme Programming (XP) method is an object-oriented method that can assist in designing and building an application according to the needs and needs of the author’s users. The data collection method used by the author in this study consisted of observation, interviews and literature study. Meanwhile, for visual modeling, it uses the UML (Unified Modeling Language) model which consists of Use Case Diagrams, Sequence Diagrams, Activity Diagrams and Class Diagrams. Hopefully this application can help the head of the equipment section in managing inventory of goods, as well as the head of the BPKH 1 Medan center in monitoring stock data.